Chimerism and donor-specific nonreactivity 27 to 29 years after kidney allotransplantation - Starzl, T E; Demetris, A J; Trucco, M; Zeevi, A; Ramos, H; Terasaki, P; Rudert, W A; Kocova, M; Ricordi, C; Ildstad, S (LIPPINCOTT WILLIAMS & WILKINS, 1993)
Chimerism was demonstrated with immunocytochemical and/or polymerase chain reaction techniques in kidney allografts and in the native skin, lymph nodes, or blood of 5 of 5 patients who received continuously functioning renal transplants from 1 or 2 haplotype HLA mismatched consanguineous donors (4 parents, 1 aunt) 27-29 years ago. In the 4 cases where the kidney donor still was alive to provide stimulator lymphocytes for testing, these provoked no (n = 2) or modest (n = 2) MLR in contrast to vigorous MLR to third party lymphocytes. In all 4 cases, the donor cells failed to generate in vitro cytotoxic effector cells (cell-mediated lymphocytotoxicity). These findings are in accord with the hypothesis that cell migration, repopulation, and chimerism are seminal events that define graft acceptance and ultimately can lead to acquired donor-specific nonresponsiveness (tolerance).